rDNA insulin glargine U300 – a critical appraisal - Wang F (Dove Medical Press, 2016)
Fei Wang,1 Stefanie Zassman,1 Philip A Goldberg2 1Department of Pharmacy Practice, School of Pharmacy, University of Connecticut, Storrs, CT, USA; 2Department of Internal Medicine, Section of Endocrinology, Yale University School of Medicine, New Haven, CT, USA Background: As the first once-daily basal insulin analog, insulin glargine 100 U/mL (Gla‑100; Lantus®) rapidly evolved into the most commonly prescribed insulin therapy worldwide. However, this insulin has clinical limitations. The approval of new basal insulin analogs in 2015 has already started to alter the prescribing landscape.Objective: To review the available evidence on the clinical efficacy and safety of a more concentrated insulin glargine (recombinant DNA origin) injection 300 U/mL (Gla-300) compared to insulin Gla-100 in patients with type 1 and type 2 diabetes mellitus (T1DM and T2DM).Methods: The following electronic databases were searched: PubMed and MEDLINE (using Ovid platform), Scopus, BIOSIS, and Google Scholar through June 2016. Conference proceedings of the American Diabetes Association (2015–2016) were reviewed. We also manually searched reference lists of pertinent reviews and trials.Results: A total of 6 pivotal Phase III randomized controlled trials known as the EDITION series were reviewed. All of these trials (n=3,500) were head-to-head comparisons evaluating the efficacy and tolerability of Gla-300 vs Gla-100 in a diverse population with T1DM and T2DM. These trials were of 6 months duration with a 6-month safety extension phase.Conclusion: Gla-300 was as effective as Gla-100 for improving glycemic control over 6 months in all studies, with a lower risk of nocturnal hypoglycemia significant only in insulin-experienced patients with T2DM. Overall, patients on Gla-300 required 10%–18% more basal insulin, but with less weight gain compared with Gla-100. Keywords: basal insulin, glargine 300 U/mL, glargine 100 U/mL